Human Motivation in Not-for-profit Organization; case Study Kebun Seni Taman Sari - Pianaung, Andre Ananta; Rudito, Bambang (Journal of Business and Management, 2012)
Motivation is connected with desire and undesirable from someone live, and those was influencing by the internal and external factors. Desire it self is an attitude that base on sincerity to doing something that compliance with believe an incentive. undesirable it self is an attitude to doing something that compliance with unbelievers about the incentive that will be achieved. Those attitude influences by internal factors like believes and external factors like influence from environment. Motivation problems that basically influencing the performance of the organization. If we look from the Human Resource point of view, an organization performance depend on the members or employees motivation. Specially for the non profit organization. Because of that aspect, human resource management will be a big discussion for merge the vision cross the members and keep their spirit for built an not-for-profit Organization that they pioneered. The purpose of this final project is to achieve some solutions for motivation problems in Kebun Seni members, and during the making process, this final project will analyze about motivation in Kebun Seni based on present theories in human resource study in order to maintain its sustainability and the commitment from the members to achieve this organization mission.Keywords— Motivation, Not-for-Profit Organization, Kebun Seni Taman Sari, Hierarchy of Needs.